ESTUDO DE ARTICULAÇÕES TEMPOROMANDIBULARES COM RESSONÂNCIA MAGNÉTICA EM PACIENTES COM ARTRITE REUMATOIDE - Tamelini, Ana Maria (2021)
Introduction: Rheumatoid Arthritis (RA) is a chronic autoimmune disease characterized by an inflammatory process of the synovial joints. Therefore, the RA can also affect the temporomandibular joint (TMJ). Studies using different appraisal methods have reported the frequency of TMJ range between 5% to 86% in RA patients. Magnetic Resonance imaging (MRI) is an imaging method with high sensitivity and specificity, but there are few studies of TMJ using this method in RA.The hypothesis of this study is that the TMJ is a joint frequently affected by RA and that it is associated with systemic disease activity and mandibular and systemic functional loss. Objectives: To describe and quantify TMJ MRI imaging findings in RA, correlate the degree of TMJ involvement with clinical and radiological alterations, disease activity and systemic and mandibular functional limitation. Methodology: A cross-sectional observational study evaluated adult patients aged 18 to 60 years, diagnosed with RA by the clinical and laboratory criteria of the American College of Rheumatology / European Laegue Against Rheumatism (ACR / EULAR 2010) screened from rheumatology clinics. The sample calculation was by non-probabilistic sampling and the sample size calculated was 44 participants by the method for finite populations in the Epi Info software (Version 6), considering the population size, 95% confidence Suavel, 5% error, prevalence 70%, probability of the event not occurring (q=0.3). 10% was added to the sample to protect possible losses and dropouts, totaling a sample of 48 participants. The subjects were interviewed using a standardized form for demographic, clinical, and laboratory information. Disease activity was assessed using the instrument Disease Activity Score 28 (DAS 28). TMJ Functional Limitation Index questionnaire was used using the Mandibular Function Impairment Questionnaire (MFIQ) and general disability was measured using the Health Assessment Questionnaire (HAQ). A standard questionnaire from the MR services for Biosafety was used and an informed consent form was obtained. The TMJ examinations were performed in a 1.5 T MRI equipment (Tesla), Intera model (Philips), with protocol without and with intravenous contrast. The patients were anonymized by the DICOM anonymyzer program and the evaluation of MR images was performed by two (02) radiologists blinded using the criteria of the German Scoring System. Interobserver and intraobserver agreement was assessed with 20% of the sample (total of 10 individuals and 20 joints) using the Intraclass Agreement Coefficient (ICC) method for quantitative variables. Statistical analysis used univariate analysis to describe the population profile, as well as the t test to analyze the relationship between independent variables and the outcome. Multiple Linear Regression was used to analyze the relationship of a set of independent variables and temporomandibular alterations. Results: 50 RA patients were included and 100 TMJs were analyzed by MRI between August and September 2020. The mean age was 49.2 ± 8 years and 92% were female, 47% had a family history and 47% were using some disease-modifying drug (DMARD). The majority resident in the municipality of Serra (41%), mixed race (50%), has completed high school (42%), are houseworkers (31%) and 15% are retired. Most have MFIQ with grade 4 impairment (68%) and severe degree of limitation (70%), DAS-28 with intense activity (48%) and HAQ with moderate disability (44%), with 52% with time since diagnosis of AR less than 10 years and 48% greater than 10 years. The profile of changes in TMJ MRI according to the Germam Scoring System showed that more than 80% of the patients had some change suggestive of disease activity and more than 50% had some degree of chronicity, 84% had synovitis, 82% had joint effusion, 48% bone edema, 54% erosions and 52% deformity of the mandibular condyle. Joint effusion had an inverse association with longer time since diagnosis (OR = 0.098; 95%CI = 0.011 - 0.855; p=0.0035) and with the use of corticosteroids (OR = 0.218; (95%CI = 0.050 - 0.950; p-value) = 0.00657), in the right joint. Medullary edema was positively associated with a greater number of joints with arthritis (OR = 5.417; 95%CI = 1.346 - 21.799; p=0.00559. Synovitis was inversely associated with education. Complete higher education). was associated with less synovitis (OR = 0.041; 95%CI = 0.004 - 0.437; p = 0.00322. The results of the Multiple Linear Regression indicated that clinical-demographic variables were independent risk factors for changes in MRI: Shorter time of diagnosis risk for joint effusion (OR= 11.5, p=0.028), 95%CI(1.310-101.180); disease activity (OR=7.093, p=0.018), 95%CI(1.409-35.701) and arthritis (OR= 5.416, p=0.017), 95%CI(1.345-21.799) was risk for medullary edema; use of DMARD (OR=11.00, p=0.035), 95%CI (1.186-101.979) was risk for erosions; ity was risk for synovitis (OR=6.533, p=0.030), 95%CI (1.199-35.573); and age for condyle deformity (OR= 39.608, p=0.037), 95%CI(1.244- 1.261.094). Conclusion: It is concluded that inflammatory lesions on MRI of temporomandibular joints are frequent and correlate with disease activity (DAS28 index) and also with indices that measure functional limitation (MFIQ and HAQ).